Digital marketing strategy an integrated approach to online marketing - Kingsnorth, Simon
"Build an effective and practical digital strategy with this bestselling guide to digital marketing, covering everything from automation and analytics to integrating AI. Digital Marketing Strategy is a global bestseller, and a one-stop guide to digital marketing and how to structure and build a more strategic approach. Recommended by the Chartered Institute of Marketing (CIM), a professional marketing body. Now fully updated, this third edition covers the integration of AI in marketing, marketing automation and how to use digital analytical tools, plus new strategies for third-party data and privacy protection. Digital Marketing Strategy will show you how to effectively select, align and manage digital channels and operations, to streamline a winning digital marketing strategy for measurable, optimized results. Learn from real-world case studies including Coca-Cola, MoneySupermarket.com, Bloom & Wild, Airbnb, Adidas, Uber so you can view best-practice examples so you can build your own digital marketing strategy. Accompanying online resources consist of practical implementation guides spanning SEO, paid-search, email, lead-generation, as well as lecture slides and activity sheets. This is an invaluable guide for digital marketing students and entry-level to mid-management professionals"--Provided by publisher.